Kajian Kebolehupayaan Sistem Penuaian Air Hujan (SPAH) sebagai Alternatif Mengurangkan Masalah Kekurangan Air Di Felda Waha, Kota Tinggi, Johor - Sudarmo, Nursyakina; Shareh Musa, Sharifah Meryam; Zainal, Rozlin; Kassim, Narimah; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
Rainwater Harvesting System (SPAH) is a system that can store rainwater in an organized place in a set quantity. The increase in demand for treated raw water has prompted the government to introduce the SPAH method as an alternative measure to provide water supply to the population. There are three objectives in this study, namely to identify issues and problems in the implementation of rainwater harvesting system in Felda Waha, identify the appropriate SPAH tank design and recommend the use of SPAH to reduce water shortage in Felda Waha, Kota Tinggi, Johor. The methodology used in this study is study design, data collection and data analysis. The preliminary study was the first stage used in the study design followed by literature review, data collection, data analysis and discussion. For this study, only focus on three parties, namely Felda Waha Manager for Felda Bukit Waha Cluster, Felda Bukit Easter Manager and Felda Simpang Waha Manager. The method of data collection was obtained from the literature review through primary data that is through qualitative methods. Secondary data is also used through scientific sources such as articles, books, journals, and authentic sources from websites. The result of the study obtained to achieve objective one is that Felda Waha has experienced water shortage issues and problems since this felda was opened. As for the results of the study for the second objective, the Felda needs funds and monthly payments for SPAH to be fully applied in the residents’ housing. The results of the study for the third objective, understanding should be given clearly and explicitly through the process of notice and notification to the population for good reception. It is hoped that this study can add more knowledge about SPAH and how to implement it. Therefore, SPAH is able to provide a solution to the residents of Felda Waha in facing the issue of lack of clean water during the dry season.